Keller‑Box Analysis of Inclination Flow of Magnetized Williamson Nanofluid - Anwar, Muhammad Imran; Rafique, Khuram; Misiran, Masnita; Shehzad, Sabir Ali; Ramesh, G. K. (Springer Nature Switzerland, 2020)
The main purpose of the current investigation is to report the numerical solution of the thermal radiations and MHD effect on the laminar flow of an incompressible Williamson nanofluid. Further, the effect of Brownian motion and thermophoresis on the flow field are considered. Compatible similarities are implemented on the flow equations to obtain the nonlinear ordinary differential equations. The numerical solution of the governing differential equations is obtained via the Keller box scheme. Findings exhibit that the energy and mass transport moderates with the growth of inclination factor along with Brownian motion effect. The temperature profile increases with the radiations factor attains a peak, which is useful for the industrial procedures. The velocity profile increases for the higher magnitudes of buoyancy factor